An unidentified fragment in the row of hero stones - Temples of India Project Team (Jio Institute, 2024)
This is an unidentified fragment in the row of hero stones that are kept in the premises of Suswani Mata Temple. Today, the stone fragment is wrapped in a red paper sheet and revered by some as Ganesha. The original style and composition of the stone fragment are not known. The newly wrapped paper serves as an attempt to make the resemble Ganesha.